Effectiveness of a Treadmill Training Programme in Improving the Postural Balance on Institutionalized Older Adults - Natalia Moya Pereira; Marcel Jean Pierre Massè Araya; Marcos Eduardo Scheicher (Journal of Aging Research)
Background. Institutionalized older adults have increased gait and balance impairment compared with community-dwelling older adults. The use of the treadmill for the rehabilitation process has been studied in different groups, but not in the institutionalized elderly. Objectives. The objective of this study was to assess the effects of a treadmill walking workout program on the postural balance of institutionalized older adults. Methods. Postural balance was assessed by the Berg Balance Scale (BBS), Short Physical Performance Battery (SPPB), gait speed, and Timed Up and Go Test (TUG) on 37 institutionalized older adults (23 in the intervention group and 14 in the control group). Training consisted of a 20-minute treadmill walking workout carried out twice a week for 10 weeks. Measurements were obtained before and after 10 weeks and with 1 month of follow-up for the intervention group. For the control group, the data were obtained before and after the training period. Results. Significant improvement occurred in all motor function parameters (BBS: p<0.01; gait speed: p<0.001; SPPB: p<0.001; and TUG: p<0.001). Conclusions. The present results permit us to conclude that a treadmill walking program had positive effects on the postural balance of institutionalized older adults.